SIMBOLISASI PADA RANCANGAN ARSITEKTUR GEREJA KATOLIK SANTO PETRUS DAN GEREJA KATOLIK SANTA PERAWAN MARIA TUJUH KEDUKAAN DI KOTA BANDUNG - Chrisylla, Meielisa (ARTEKS Jurnal Teknik Arsitektur, 2016)
Title: Architectural Design Symbolism Catholic Church of Saint Peter and The Virgin Mary Catholic Church Santa Grief Seven in BandungAs a place of holy worship, a Catholic Church should posses a sacred interior and exterior expression. Modernization has caused a good deal of this sacred expression of the Catholic Church to fade. As Catholic Church is a place of worship that supports all liturgical activities, semiotic theory are used toanalyze and decipher its architecture to preserve sacredness. The research methodology that was employed was qualitative methods using Peirce’s semioticprinciples and their implementation in Church architecture. The principle was then used to analyze two case studies in every detail of their draw up. The area of planning encompassed: (1) Scope of the surrounding environment; (2) Scope of the site; (3) Scope of the form. This analysis employed semiotic principles that were elaborated with Catholic Church principles to create a guideline in thearchitectural planning of a Catholic Church. The purpose of this research is to find the most dominant sacral expression between Santo PetrusChurch and the Santa Perawan Maria Tujuh Kedukaan Church by means of the symbols attached to the architectural elements between these two Catholic Churches.The results of this study were that sacral expression in terms of (1) Scope of the surrounding environment; (2) Scope of the site; (3) Scope of the form are more dominant in the Santo Petrus Church compared to the Santa Perawan Maria Tujuh Kedukaan Church.Keywords: Peirce’s semiotics, sacral expression, catholic church